2001
DOI: 10.1007/s003590100184
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic detection and communication by decapod crustaceans

Abstract: This paper reviews behavioral, physiological, anatomical, and ecological aspects of sound and vibration detection by decapod crustaceans. Our intent is to demonstrate that despite very limited work in this area in the past 20 years, evidence suggests that at least some decapod crustaceans are able to detect and use sounds in ways that parallel detection and processing mechanisms in aquatic and terrestrial vertebrates. Some aquatic decapod crustaceans produce sounds, and many are able to detect substrate vibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
146
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(154 citation statements)
references
References 0 publications
1
146
0
7
Order By: Relevance
“…Upon approach, individuals waved their brightly colored chela in the air while simultaneously producing a sound-resulting in a multimodal display (visual + acoustic) that presumably functions to warn off predators. Acoustic communication is well known among different groups of crustaceans (Müller 1989;Popper et al 2001), and the combination of visual and acoustic signals has already been reported in mating contexts (e.g., singing and dancing in the ghost crab Ocypode platytarsus- (Clayton 2008)). Although our focus in this chapter has been limited to multimodal signals incorporating chemical components, crustaceans likely encompass numerous examples of multimodal signals that combine other sensory modalities.…”
Section: Future Directionsmentioning
confidence: 99%
“…Upon approach, individuals waved their brightly colored chela in the air while simultaneously producing a sound-resulting in a multimodal display (visual + acoustic) that presumably functions to warn off predators. Acoustic communication is well known among different groups of crustaceans (Müller 1989;Popper et al 2001), and the combination of visual and acoustic signals has already been reported in mating contexts (e.g., singing and dancing in the ghost crab Ocypode platytarsus- (Clayton 2008)). Although our focus in this chapter has been limited to multimodal signals incorporating chemical components, crustaceans likely encompass numerous examples of multimodal signals that combine other sensory modalities.…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, it has been shown that sound is an important cue for many decapod crustaceans and fish larvae to orient (Simpson et al, 2005;Radford et al, 2007) to and settle (Radford et al, 2011;Stanley et al, 2012) in appropriate habitats. More recently, it has been found that crabs have the ability to produce sounds (Popper et al, 2001;Buscaino et al, 2015), although the behavioral significance of these sounds is yet to be determined. It must be noted, underwater sound is comprised of two components, particle motion and sound pressure, with particle motion being the acoustic stimulus detected by marine animals.…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been little research investigating whether decapod crustaceans are capable of detecting underwater sound. For a comprehensive review of crustacean hearing mechanisms see Popper et al 2001. Statocysts in crustaceans are balancing organs that consist of complexly folded invaginations of the cuticle that form a canal system in the basal segment of the first antenna (Fraser, 1981). It has been well established that the crustacean statocyst functions as an equilibrium organ, by initiating correction behaviors of the animals in 3 dimensional space and in sound reception (Budelmann, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sound travels fast through water (Urick, 1983) and is capable of conveying significant information over long distances. Many marine organisms make sounds: marine mammals (Erbe, 2012;Richardson et al, 1995;Southall et al, 2007;Tyack & Clark, 2000), fish (Bass & Ladic, 2008;Popper et al, 2003;Hawinks & Myrberg, 1983;Myrberg, 1978Myrberg, , 1980Tavolga, 1971) and invertebrates (Buscaino et al, 2011;Popper et al, 2001). These organisms reveal their presence and behavioral dynamics through acoustic signals that can be easily detected, recorded, saved, and analysed.…”
Section: The Application Of Soundscape Ecology To Protect the Meditermentioning
confidence: 99%